1988
DOI: 10.1177/00220345880670020901
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Bonding of Prosthodontic Adhesives to Dental Alloys

Abstract: In vitro tensile bond strengths were determined for three adhesive cements and two resin-bonded bridge cements to two alloys, each prepared by two methods: sandblasted Ni-Cr-Be alloy (I), electro-etched Ni-Cr-Be alloy (II), sandblasted Type IV gold alloy (III), and tin-plated Type IV gold alloy (IV). Storage conditions of 24 hours at 37 degrees C and 30 days at 70 degrees C were evaluated. The highest bond strengths were obtained for the electro-etched Ni-Cr-Be alloy, and all bond failures were cohesive. At bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2
13

Year Published

1990
1990
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 3 publications
2
30
2
13
Order By: Relevance
“…A mixed fracture pattern with cohesive predominance of Panavia F was obtained in this study, a constant feature in studies using this type of resin cement 22,26 .…”
Section: Discussionsupporting
confidence: 72%
“…A mixed fracture pattern with cohesive predominance of Panavia F was obtained in this study, a constant feature in studies using this type of resin cement 22,26 .…”
Section: Discussionsupporting
confidence: 72%
“…Panavia F 2.0 resin cement contains MDP monomer (10-Methacryloyloxydecyl dihydrogen phosphate), which can react chemically with the chromium oxide layer created on the cast metal surfaces (21,22) by means of covalent bonds (13). in the present study, the alloy primer was not used, in spite of being indicated by the manufacturer for application on the metal surface before cementation of the resin material.…”
Section: Resultsmentioning
confidence: 89%
“…On promoting adhesive bonding as well as surface modification of substrate materials, the type of functional monomer contained in a resin cement or primer plays an influential role. Although the use of some phosphate or carboxylic monomers has been shown to improve the bond strength of resins to base metal alloys, these monomers were not as effective for noble metal alloys [6][7][8] . To bond noble metal alloys, additional surface modification treatments such as tin plating 9) , high temperature oxidation 10) , galliumtin alloy technique 11) , and silica coating 12) were devised.…”
Section: Introductionmentioning
confidence: 99%